Chapter "Dante, Can I Lead You?" South African students write back (across seven centuries and a hemisphere) - Thurman, Christopher (Studi e saggi, 2021)
This account of the essays, poems and stories collected in the present volume reflects on the authors' diverse forms of engagement with Dante via the implications of proximity and distance. In what ways do these students signal affinity with Dante - his historical context, his writerly persona - and in what ways do they subvert or challenge the world view (or the cosmic order) represented in the Commedia? How does their location in South Africa in the twenty-first century, as a particular kind of temporal and spatial dislocation from Italy in the fourteenth century, enable their creative and critical responses to Dante's work?